Imaging spectrum and prevalence of variant branching pattern of aortic arch - K. V., Vipin Krishnan; Narayan, Varun; Ibrahim, Niyaz; Mathew, John; James, Sheen Maria (International Journal of Research in Medical Sciences, 2019)
Background: Variant branching patterns of the aortic arch are not infrequent but are commonly under reported. This study was conducted to determine the spectrum of Variant branching pattern of aortic arch and their prevalence using contrast enhanced computed tomography (CECT) images of the cases from a tertiary care centre. Methods: Contrast enhanced computed tomography (CECT) images of aortic arch region from 1116(629 male and 487 female) cases from 18 to 85 years of age were examined retrospectively. The images were reviewed for normal and variant anatomy of aortic arch and the results were analyzed statistically. Results: Of 1116 patients, 878 (78.6%) cases showed normal and 238 (21.3%) cases had variant branching pattern of the aortic arch. The most common variation was the common origin of brachiocephalic trunk (BCT) and the left common carotid artery (LCCA) which was observed in 160 (14.3%) cases. In 8 (0.7%) cases, BCT and LCCA took origin from a single common trunk arising from the aortic arch. In 60(5.4%) cases, the left vertebral artery (LVA) originated directly from the aortic arch between the origin of the LCCA and left subclavian artery (SCA). 8 (0.7%) cases had aberrant right subclavian artery. Two (0.2%) cases showed right aortic arch. Conclusions: Interventional radiologists and surgeons should be well aware of variant anatomy of aortic arch. Contrast CT is a highly reliable imaging method for demonstrating anatomical features and variations of the arch.